Mass Balance of Four Mongolian Glaciers: In-situ Measurements, Long-Term Reconstruction and Sensitivity Analysis - Khalzan, Purevdagva; Sakai, Akiko; Fujita, Koji (Frontiers in Earth Science, 2022)
This study describes the in situ observed and modeled mass balances of four representative glaciers in the Mongolian Altai Mountains. Mass-balance stakes and automatic weather stations (AWS) were installed along each glacier to obtain the in situ mass balances and meteorological variables. We calibrate the ERA5 meteorological variables using the observed values, then estimate the precipitation parameters to obtain the observed point mass balances using an energy- and mass-balance model. We evaluate the mass-balance profile and glacier-wide mass balance via a mass-balance model using the calibrated ERA5 data and estimated precipitation parameters to fill in the spatial and temporal gaps in the stake networks and AWS measurements. We demonstrate that almost all of the observed mass balances have been in a negative state since 2003. We also reconstruct the long-term mass balances for the 1980–2018 period, which range from −760 to −160 mm water equivalent under the different climatic conditions (annual precipitation varies from 190 to 860 mm). We further evaluate the mass-balance sensitivities to temperature and precipitation changes. We confirm that both sensitivities correlate significantly with the annual precipitation; increased precipitation yields more negative sensitivity to temperature changes and less positive sensitivity to precipitation changes.